Evaluation of 10 Genotypes of Rapeseed (Brassica napus L.) Under NaCl Salinity Tolerance - Saima, Shehzadi; Ahmad, Irshad; Javed, Ayesha; Anila, Iram; Ijaz, Kiran; Ghazal, Ureesa; Hashim, Muhammad (Indus Journal of Bioscience Research, 2025)
Soil salinity is the serious abiotic stress that affects plant growth attributes along with physiology and biochemical processes through osmotic stress, which consequently reduced biomass production. This adverse effect of salt stress appears on all growth stages including germination, seedling, vegetative and maturity. However, tolerance to salt stress at different plant developmental stages varies from species to species. The present research work was conducted to explore the impact of salts stress on ten varieties of rapeseed (Sandal canola, Rainbow, Legend, Punjab canola, Dunkled, Oscar, AC Excel, Super canola, Shiralee and Faisal canola) and to screen the best salt tolerant variety of Rapeseed. Seeds were sown in plastic trays of (70x50cm) to check their germination under salt stress in Lab experiment. Four treatments were prepared with control (0 mM) and three NaCl treatments (50, 100 and 150 mM). The results showed that at 150Mm levels of salinity germination occurred, but at low level as compared to other treatments (0, 50 and 100 mM). Different parameters such as germination percentage, shoot and root length and shoot and root weights (both fresh and dry) showed considerable variations. Germination percentage, root and shoot length and root and shoot weights decreased in all varieties with the increase of salt concentration. However, Shiralee and Super canola showed the highest germination and well growth in all parameters considered as resistant to salt stress while Punjab canola and Oscar showed less germination regarded as sensitive to salinity. Other varieties showed intermediate values in terms of germination and shoot and root fresh and dry weights.